Aerodynamic stability of typical sea-crossing bridge with streamlined box girder under wave-interfered complex wind fields. Issue 228 (September 2022) - Yu, Enbo; Jin, Yuanjie; Xu, Guoji; Han, Yan; Li, Yongle
Abstract: Tropical cyclones landing on the coast are usually associated with both strong winds and waves, posing a major threat to sea-crossing bridges. Strong waves riding on the elevated storm surge squeeze the narrow gap between the sea surface and bottom of the bridge deck, thus complicating the wind field and leading to different bridge nonlinear flutter responses as compared with the steady flow field. In this study, to evaluate the bridge safety under such circumstances, wind tunnel test was carried out for a typical sea-crossing bridge with streamlined box girder based on a developed dynamic response test system for simulating the coupling effect of wind, wave, and current on bridges, where the clearance, underneath the bridge deck, and wave speed can be systematically adjusted to investigate the wind field characteristics and bridge nonlinear flutter response. Numerical simulation with the LES (large eddy simulation) scheme was employed to successfully visualize the wind field around the bridge and the mechanism of the nonlinear flutter response was analyzed in detail. The results of this preliminary investigation show that: (a) In the wind tunnel tests, when the wave crest passes under the bridge, the acceleration effect due to the narrow gap can lead to an increase for the nonlinear flutter amplitude of the bridge, which threatens the structural safety; (b) The measured wind speed at the bridge site exhibits strong turbulence intensity and non-Gaussian distribution tendency; and (c) Based on the numerical simulation, the airflow between the wave crest and the main structure features a large vertical velocity component, leading to a large AOA (angle of attack) value of the incoming flow. Meanwhile, the air pressure around the girder is unevenly distributed, thus unavoidably weakening the aerodynamic stability of the bridge. Highlights: The non-linear bridge flutter stability is analyzed by simulating the wave-interfered wind field in the wind tunnel test. Wave-interfered wind field characteristics are studied experimentally and numerically. The bridge non-linear flutter response is closely related to the spatial relationship of wave and bridge.